2012
DOI: 10.1002/ange.201204440
|View full text |Cite
|
Sign up to set email alerts
|

Mit N‐heterocyclischem Gallylen stabilisierte niedervalente Ge2‐ und Ge4‐Spezies

Abstract: Viel π und kein σ! Im Ga2Ge2‐Kern von Ge2[Ga(DPP)]2 liegt einer ausführlichen theroretischen Analyse zufolge zwischen den beiden Ge‐Atomen keine σ‐Bindung vor, eine transannulare π‐Bindung hingegen schon (siehe Bild). Die Verbindung entsteht bei der Reduktion von (PCy)3⋅GeCl2 mit Ga(DDP)/KC8, die als ein weiteres Produkt auch Ge4[Ga(DPP)]2 mit einem Ge4‐Tetraeder liefert. DDP = HC(CMeNC6H3‐2,6‐iPr2)2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 35 publications
(22 reference statements)
1
3
0
3
Order By: Relevance
“…i The absorption band was assigned to the HOMO(ψ S )–LUMO(ψ A ) electronic excitation of the π single‐bonding system (Figures 1 and 2, and Scheme ). The assignment was confirmed by time‐dependent (TD) DFT calculations 10. As shown in Figure 2 and Table 1, the absorption maxima were not significantly dependent on the alkoxy group.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…i The absorption band was assigned to the HOMO(ψ S )–LUMO(ψ A ) electronic excitation of the π single‐bonding system (Figures 1 and 2, and Scheme ). The assignment was confirmed by time‐dependent (TD) DFT calculations 10. As shown in Figure 2 and Table 1, the absorption maxima were not significantly dependent on the alkoxy group.…”
Section: Resultssupporting
confidence: 60%
“…Very recently, Fischer and Frenking et al. reported a π single bond in a Ge 2 Ga 2 four‐membered molecule 10. Diradicals H ‐ DR2 3, 6a, 11, 12 belong to Type‐2 molecules because the n orbital of the lone‐pair electrons of N, O, and P interact with ψ S .…”
Section: Introductionmentioning
confidence: 99%
“…[19] The chemistry of the planar singlet diradicaloids has been extensively studied using the extremelyl ong-lived singlet 2,2-dialkoxypropane-1,3-diyls pl-1 DR5 (Ar = Ph, X = OMe; l max at % 570 nm, [20] and the diradicaloidso fh eterocyclic systems. [21][22][23][24][25][26][27][28][29] In this study ac urious absorption band with l max at % 450 nm was found together with the planar singlet diradical pl-1 DR6 with l max at % 580 nm during the photochemical denitrogenation of AZ6 [30] bearing stericallyh indering substituents Ar (= dimethoxyphenyl) and X( = OCH 2 Ph). Based on product analyses, spectroscopic observations, and high-levelc omputational studies, the absorption signal at % 450 nm was assigned to the third isomer in the homolysis, that is, the puckered singlet diradicaloid puc-1 DR6 (Scheme 2).…”
Section: Introductionmentioning
confidence: 86%
“…Letztere Struktur leitet sich von einem Ge4‐Tetraeder ab, bei dem zwei Gallium‐β‐diketiminateinheiten in je eine Kante eingeschoben sind. Quantenchemische Berechnungen zeigen die Existenz einer transannularen π‐Bindung zwischen den beiden Germaniumatomen im Ga2Ge2‐Vierring ohne ρ‐Bindung 68…”
Section: Highlights Aus Der Gruppe 14unclassified